Law Enforcement, Municipal Budgets and Spillover Effects: Evidence from a Quasi-Experiment in Italy - Sergio Galletta (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this paper, I empirically investigate the presence of spillover effects resulting from the strengthening of law enforcement against corruption and organized crime in local governments. Specifically, I take advantage of an Italian law that gives power to the central government to replace democratically elected municipal officials who are potentially connected with mafia with a commission of non-elected administrators. Fixed effects model estimates that focus on a sample of municipalities from three Italian regions (Campania, Calabria and Sicilia) for the period 1998 to 2013 show that the city council dismissal of a municipality fosters a reduction in public investments in neighboring municipalities. Additional empirical evidence suggests that this result could be explained by the presence of law enforcement spillovers potentially reducing misconducts in neighboring municipalities.
Keywords: D73; E62; E72; K42; 330; horizontal interaction; Italy; mafia; corruption